Dexamethasone in Prevention of Postextubation Stridor in Ventilated Children: A Randomized, Double-blinded, Placebo-controlled Trial - Ritu (Indian J Crit Care Med, 2020)
BACKGROUND AND AIMS: Postextubation stridor (PES) is a serious complication in ventilated patients which increases the length of stay in intensive care units (ICUs). We studied the efficacy of dexamethasone in prevention of PES in ventilated children. MATERIALS AND METHODS: A randomized, double–blinded, placebo-controlled trial was carried out in pediatric ICU. Children (2 months to 12 years) who underwent mechanical ventilation for 48 hours were randomized into two groups to receive either dexamethasone at 0.15 mg/kg/dose or normal saline for 6 doses with first dose given 6–12 hours prior to planned extubation. Patients were hourly monitored for vital signs and appearance of stridor using Westley croup score (WCS) within 72 hours after extubation. Whenever the score exceeded 4, nebulized adrenaline (1:1,000 at 0.5 mL/kg/dose) was given. The primary outcome was occurrence of PES. RESULTS: Dexamethasone group comprised of 42 children while placebo group had 38 children. Baseline characteristics of two groups were similar. Overall PES occurred in 48.7% patients, 42.8% (18/42) in dexamethasone group, and 55.2% (21/38) in placebo group [p = 0.26, odds ratio (OR) 95% confidence interval (CI) = 0.60 (0.25–1.47)]. WCS >4 was present in 28.5% (12/42) of dexamethasone group vs 47.3% (18/38) of placebo group [p = 0.08, OR (95% CI) = 0.37 (0.12–1.06)]. There was no difference in reintubation rates in two groups [p = 0.9, OR (95% CI) = 1.06 (0.32–3.51)]. CONCLUSION: We found no beneficial role of the studied dose of dexamethasone (0.15 mg/kg) over placebo on the incidence of PES. HOW TO CITE THIS ARTICLE: Ritu, Jhamb U. Dexamethasone in Prevention of Postextubation Stridor in Ventilated Children: A Randomized, Double-blinded, Placebo-controlled Trial. Indian J Crit Care Med 2020;24(12):1230–1235.